Clinical Outcomes of a Multidisciplinary Female Chronic Pelvic Pain Program. Issue 12 (December 2021) - Westbay, Lauren C.; Adams, William; Kistner, Margaret; Brincat, Cynthia; Bresler, Larissa; Yang, Linda C.; Fitzgerald, Colleen M.
Abstract : Objective: The aim of this study was to describe patient-reported longitudinal outcomes in a multidisciplinary female chronic pelvic pain (CPP) program. Methods: We conducted a retrospective cohort study for women cared for in a tertiary, multidisciplinary, female (CPP) program between 2012 and 2017. Patient demographics were collected from electronic medical records. Patients completed the numerical rating scale for pain, Pain Disability Index (PDI), and Patient Global Impression of Improvement scale at each visit. Mixed-effects models were used to assess change in patient responses over time. Results: Patients (N = 317) with a mean age of 44.3 years (SD, 14.6) and median duration of symptoms of 3 years (interquartile range, 1.0–7.0) were assessed in this analysis. The primary diagnosis was pelvic floor myofascial pain (67%). On multivariable analysis, numerical rating scale scores decreased by −0.11 point [95% confidence interval (CI), −0.20 to −0.01] every 3 months ( P = 0.03). On multivariable analysis, total PDI score decreased by −0.88 point (95% CI, −1.43 to −0.33) ( P = 0.003), and PDI sexual subscores decreased by −0.29 point (95% CI, −0.44 to −0.14) ( P < 0.001) every 3 months. A higher (worse) Patient Global Impression of Improvement score was associated with a higher (worse) PDI score at follow-up (odds ratio, 1.04; 95% CI, 1.01–1.07; P = 0.01). Conclusions: Patients in a multidisciplinary CPP program demonstrated improvement over time in pain disability that was associated with an overall global impression of improvement.